If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+2=6(x-2)-7
We move all terms to the left:
7x+2-(6(x-2)-7)=0
We calculate terms in parentheses: -(6(x-2)-7), so:We get rid of parentheses
6(x-2)-7
We multiply parentheses
6x-12-7
We add all the numbers together, and all the variables
6x-19
Back to the equation:
-(6x-19)
7x-6x+19+2=0
We add all the numbers together, and all the variables
x+21=0
We move all terms containing x to the left, all other terms to the right
x=-21
| 3x+2=10−3x | | 5^2x-2+4•5^x-21=0 | | -2(x-8)+8=5(x+3) | | 47x/60=560 | | 0.04x=5000 | | 3n(4+7)=8 | | (15x-2)+(7x+4)=90° | | 90+b+(b+45)+(2b-90)+3/2b=540 | | C=9/2(k-28) | | 17-2q=67 | | 5(x+10)+2=-11(x-6)-1 | | 0.18(y-5)=0.04=0.06-2.1 | | 1.5(2x+6)=21 | | 100y+200=3300 | | 3(2x-1)-2(7x-3)=4x-15 | | 2y+10=7 | | 4(2x+4)=9x-7 | | -3k+3(k-6)=18 | | 2x(x)+5x-4=0 | | 4e+9=5e+3 | | 5(4x+5)=3x+4 | | 4x(4-6)=23 | | 11x+6=8x30 | | 8x-10=2x-1 | | a+(3a/2)+(3a/4)=390 | | 1.1=3x-2.5 | | 3x+11=2x+5(x-1) | | 9n^2+n+7=0 | | 3(x-2)−2x+3= −12 | | 4(-2n-6)=-3(1+n)=2n | | 3(x−2)−2x+3= −12 | | 3(x−2)−2x+3=3(x−2)−2x+3= −12−12 |